Single-Event Burnout Mechanisms in SiC Power MOSFETs - Witulski, Arthur F.; Ball, Dennis R.; Galloway, Kenneth F.; Javanainen, Arto; Lauenstein, Jean-Marie; Sternberg, Andrew L.; Schrimpf, Ronald D. (IEEE transactions on nuclear science, 2018)
Heavy ion-induced single-event burnout (SEB) is investigated in high-voltage silicon carbide power MOSFETs. Experimental data for 1200-V SiC power MOSFETs show a significant decrease in SEB onset voltage for particle linear energy transfers greater than 10 MeV/cm 2 /mg, above which the SEB threshold voltage is nearly constant at half of the rated maximum operating voltage for these devices. TCAD simulations show a parasitic bipolar junction transistor turn-on mechanism, which drives the avalanching of carriers and leads to runaway drain current, resulting in SEB.